2016
DOI: 10.1007/s00247-016-3615-x
|View full text |Cite
|
Sign up to set email alerts
|

Resistive indices of cerebral arteries in very preterm infants: values throughout stay in the neonatal intensive care unit and impact of patent ductus arteriosus

Abstract: BackgroundLittle is known about cerebral artery resistive index values in infants born extremely preterm.ObjectiveTo report resistive index values in various cerebral arteries in a prospective cohort of preterm infants born at <29 weeks’ gestation, and to compare resistive index in these arteries and assess the relationship between resistive index and hemodynamically significant patent ductus arteriosus.Materials and methodsUsing Doppler imaging, we obtained resistive index values of internal carotid arteries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
6

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 28 publications
(31 reference statements)
2
27
0
6
Order By: Relevance
“…This is in line with previous studies demonstrating a good correlation between flow indices in the anterior and in the middle cerebral artery, 15,33 as well as between the right and left great vessels. 34 These findings support that identifying exactly the same vessel is not essential to assess the cerebral circulation. NeoDoppler can therefore be feasible for non-expert users, who can focus only on capturing a high-quality flow signal within the broad ultrasound beam.…”
Section: New Features Obtained With Neodopplermentioning
confidence: 64%
“…This is in line with previous studies demonstrating a good correlation between flow indices in the anterior and in the middle cerebral artery, 15,33 as well as between the right and left great vessels. 34 These findings support that identifying exactly the same vessel is not essential to assess the cerebral circulation. NeoDoppler can therefore be feasible for non-expert users, who can focus only on capturing a high-quality flow signal within the broad ultrasound beam.…”
Section: New Features Obtained With Neodopplermentioning
confidence: 64%
“…The internal carotid artery (ICA) was examined in two studies. 40,47 Both concluded that there was a significantly higher RI in the ICA in the presence of a hemodynamically significant PDA (median RI 0.82 in PDA versus 0.75 in controls-p < 0.001 47 and mean RI 0.97 in PDA versus 0.81 in controls-p < 0.05 40 ). The RI in the common carotid artery (CCA) and in the basilar artery and striatal and pial arteries did not show significant differences in preterm infants with and without hemodynamically significant PDA.…”
Section: Results Of Individual Studiesmentioning
confidence: 98%
“…Mean RI varied between 0.78 and 1.2 in a large PDA compared to RI of 0.61-0.81 in preterm infants without a significant PDA. 25,26,28,29,31,40,44,47 Five of these studies used the duplex method without 2D ultrasound. RI in the middle cerebral artery (MCA) was investigated in two studies, 39,40 showing a significantly higher RI in patients with PDA.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 2 more Smart Citations